The woman inside - Edvardsson, M. T. (Celadon Books, 2023)
"A wealthy couple ends up murdered in the nicest part of town in this compulsively readable, page-turning thriller from M. T. Edvardsson, The Woman Inside. Bill Olsson, recently widowed, is desperate to provide for his daughter, Sally. Struggling to pay rent, he welcomes a lodger into their home: Karla, a law student and aspiring judge, who works as a housekeeper to make ends meet. Her clients are the Rytters, an incredibly wealthy couple who hide behind closed doors. The wife is ill and hasn't left the house in months. The husband is controlling and obsessive. Is he just a worried husband, concerned for his wife's health? Or is there something more sinister at play? As Bill's situation becomes more dire, Karla is forced to make a difficult choice. And when the Rytters wind up dead, and Karla is pulled in for questioning, she's made to defend some parts of her past she'd rather not revisit. Every person in The Woman Inside is hiding something, but could any of them really have been driven to kill?"--